Comparison between our mapped (original) and predicted LULC products between the years 2010 and 2020. - Yisa Ginath Yuh (20370814) (2024)
Map products show strong correlations between the original and predicted datasets as quantified in S12A and S12B Table, suggesting the reliability of the ILCM in predicting LULCC. Map generated with the RF Machine learning model, using the UUSGS Landsat 5 and 7 Collection 2 Level 2 data, freely available for public use with no data restrictions nor permissions required: https://www.usgs.gov/faqs/are-there-any-restrictions-use-or-redistribution-landsat-data. (TIF)